Crohn’s Disease in Clinical Remission Is Marked by Systemic Oxidative Stress - Bourgonje, Arno R.; von Martels, Julius Z. H.; Bulthuis, Marian L. C.; van Londen, Marco; Faber, Klaas Nico; Dijkstra, Gerard; van Goor, Harry (Frontiers in Physiology, 2019)
Introduction: Crohn’s disease (CD) is characterized by chronic and relapsing inflammation of the gastro-intestinal tract. It is assumed that oxidative stress contributes to CD pathogenesis, but systemic biomarkers for oxidative stress in CD are not yet identified. A reduction in free thiol groups in plasma proteins (“plasma free thiols”) reflects systemic oxidative stress since they are prime substrates for reactive oxygen species. Here, we determined the concentrations of plasma free thiols in CD patients and healthy controls and studied the putative correlation with disease parameters. Methods: Free thiols were quantified in plasma of patients with CD patients in clinical remission (according to the Harvey Bradshaw Index (HBI)) and healthy controls and adjusted for plasma albumin. Albumin-adjusted free thiol concentrations were analyzed for associations with clinical and biochemical disease markers. Results: Mean plasma free thiol concentrations were significantly lower in patients with CD (n=51) compared to healthy controls (n=27) (14.7±2.4 vs. 17.9±1.8 µmol/g albumin; P<0.001). Patients with CD with above-average free thiols had significantly lower CRP levels (median 1.4 [interquartile range] [0.4;2.6] vs. 3.6 [0.6;7.0] mg/L; P<0.05) and BMI (23.6±4.8 vs. 27.1±5.2 kg/m2; P<0.05). Patients with CD having solely colonic disease demonstrated markedly reduced plasma free thiol concentrations compared to patients with ileocolonic involvement (13.2±1.8 vs. 15.2±2.2 µmol/g; P<0.05). Finally, plasma free thiol concentrations negatively correlated with biomarkers of inflammation, including hsCRP, SAA, IL-17A (all P<0.05) and VEGF. Conclusion: Plasma free thiols are reduced in patients with CD in clinical remission compared to healthy controls. Thus, subclinical CD disease activity is reflected by systemic oxidative stress and plasma free thiols may be a relevant therapeutic target and biomarker to monitor disease activity in CD.